2001
DOI: 10.1002/1522-2683(200109)22:15<3257::aid-elps3257>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis investigation on the structure-enantioselectivity relationship in synthetic cyclopeptides as chiral selectors

Abstract: We recently reported the use of a deconvolution strategy to identify the best chiral selectors for Nalpha-2,4-dinitrophenyl (Dnp) amino acid racemates from a combinatorial library composed of thousands of homodetic cyclohexapeptides. Selection was based on the capillary electrophoresis (CE) enantioresolution for a set of Dnp-amino acids. The groups involved in the chiral discrimination were assessed by nuclear magnetic resonance (NMR) spectroscopy, which revealed a strong involvement of one of the aromatic rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…NMR spectroscopy has been shown to be a powerful tool for studying enantioselective associations between a chiral selector and the analyte enantiomers in solution in various cases. For peptide enantiomer analytes investigations employing modified cyclodextrins as chiral selectors have been reported. , Conversely, the use of peptides as chiral selectors has also been studied by NMR spectroscopy. In several studies the insights into the chiral recognition mechanisms gained by NMR spectroscopy have served to interpret observations made during enantiomer separation experiments. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectroscopy has been shown to be a powerful tool for studying enantioselective associations between a chiral selector and the analyte enantiomers in solution in various cases. For peptide enantiomer analytes investigations employing modified cyclodextrins as chiral selectors have been reported. , Conversely, the use of peptides as chiral selectors has also been studied by NMR spectroscopy. In several studies the insights into the chiral recognition mechanisms gained by NMR spectroscopy have served to interpret observations made during enantiomer separation experiments. ,, …”
Section: Resultsmentioning
confidence: 99%
“…13,14 Conversely, the use of peptides as chiral selectors has also been studied by NMR spectroscopy. [15][16][17] In several studies the insights into the chiral recognition mechanisms gained by NMR spectroscopy have served to interpret observations made during enantiomer separation experiments. 12,14,[16][17][18][19][20] To study the (noncovalent) binding properties of the transient diastereomeric complexes of SO1 and the enantiomers of SA1 and SA2, respectively, a combination of several 1D and 2D NMR experiments were carried out.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…This finding suggested that the size and rigidity of the cyclopeptide system was important for ensuring chiral discrimination. In subsequent NMR studies it was recognized that the presence of aromatic moieties carrying electron-withdrawing substituents, i.e., nitro groups, were essential for enantiorecognition via π-π stacking interactions and amide/aromatic n -π interactions [47,48].…”
Section: Origin Of the Reciprocal Principle In Chromatographymentioning
confidence: 99%
“…Cyclic peptides, similar to crown ethers, cyclodextrin macrocyclic antibiotics, and chiral micelles, can be used for host–guest recognition (inclusion of host with guest by noncovalent interactions) in supramolecular chemistry, biology, and pharmacology . In addition, they have been used to recognize chiral guests and successfully applied in chiral separation technologies to identify the minute differences of the isomers . Cyclic peptides can also be used as the building blocks of nanotubular structures.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In addition, they have been used to recognize chiral guests and successfully applied in chiral separation technologies to identify the minute differences of the isomers. [12][13][14][15][16][17] Cyclic peptides can also be used as the building blocks of nanotubular structures. In the nanotubes formed from cyclic peptides, β-sheet hydrogen bonding exists between two adjacent cyclic peptides.…”
Section: Introductionmentioning
confidence: 99%